Pengaruh Kunjungan Wisatawan dan Tingkat Hunian Hotel Pada Pendapatan Asli Daerah - Aninda, Nama; Gantino, Rilla (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
One of the conditions to find out from the impact of tourism itself on the regional economy is seen from the increase in income received in the area.This can describe a good regional economy condition where the states of activity and of course improve the economy of the area visited.This study aims to describe and analyze the effect of the number of tourist visit and hotel accupancy rates on the local revenue of Bukittinggi City for the 2016-2019 period with secondary data. The data analysis technigue used in this study is the PLS variant- based SEM (Structural Equation Modeling) analysis technigue. Observations from data on the number of visits by foreign and domestic tourist from ticker sales of the cultural and the panorama of the Japanese hole as well as the occupancy rate of five- star and jesmine hotels data taken monthly data of 48 samples were used. The results of this study indicate that, first : The number of tourist visits has a positive and significant effect on local revenue. Second : The hotel accupancy rate has a negative and significant effect on local revenue.